PEMERIKSAAN KESEHATAN SEBAGAI UPAYA DETEKSI DINI PENYAKIT TIDAK MENULAR - Naimah, Siti; Agustiana Sari, Dwi; Widuri, Widuri; Santoso, Teguh (Jurnal LENTERA, 2024)
Non-communicable diseases (NCDs) is a chronic disease that often shows no symptoms at the begin of the disease, so many people are not aware that they have PTM. This incident means that the lack of efficacy in carrying out early screening for PTM can be identified by carrying out early detection by checking blood pressure, blood cholesterol levels, blood sugar and measuring Body Mass Index. The aim of this activity is to detect early risk factors for non-communicable diseases after an examination. This activity includes checking blood pressure, cholesterol levels and blood glucose levels. This activity was carried out on Sunday 7 August 2023. The location of this Community Service was carried out in Dukuh Nyamplung RT 03/ RW 06, Donoharjo Village, Ngaglik District, Sleman Regency. This activity was attended by 46. The results of the early detection of NCDs showed that 37% of residents had hypertension, 75% of residents had hypercholesterolemia and 35% had hyperglycemia.